A Holistic Approach to Sustainable Corporate Governance: Exploring the Role of Business Ethics and Technology – A Bibliometric Study - Akbar, Fitrah Azirial (Economics, Business, Accounting & Society Review, 2024)
This study explores emerging trends in Sustainable Corporate Governance literature, focusing on the integration of Business Ethics and Information Technology (IT) in Environmental, Social, and Governance (ESG) reporting. As ESG principles gain prominence, businesses face increasing pressure to ensure transparent, ethical, and technology-driven sustainability disclosures. However, ESG implementation remains inconsistent, particularly in developing economies like Indonesia, where weak regulatory frameworks, limited investor pressure, and resource constraints hinder progress. Ethical accountability is essential in enhancing ESG reporting quality, as it fosters transparency, stakeholder trust, and corporate integrity. Governance structures, such as independent boards and robust oversight mechanisms, play a pivotal role in ensuring responsible ESG disclosures and mitigating greenwashing risks. Simultaneously, advancements in IT and digital platforms facilitate real-time data collection, analysis, and dissemination, improving the accessibility and accuracy of ESG reports. The study highlights the role of business ethics in shaping ESG disclosures and the impact of information systems on sustainability reporting quality. Using co-word analysis and scientific mapping, this research identifies key intellectual structures and emerging themes in sustainable corporate governance literature. The findings emphasize the need for strategic ESG integration, where corporate governance and ethical business practices align with technological advancements to drive long-term sustainability and responsible corporate behavior. This study highlights ESG, business ethics, and digital transformation, emphasizing accountability, regulation, technology, and corporate resilience